Evaluation of Allocated Areas for Parks and their Attributes: Hail City - Said, M. A.; Touahmia, M. (Engineering, Technology & Applied Science Research, 2020)
Accessibility to parks and open spaces plays an important role in the urban quality of life. Public parks play a vital role that affects all members of society regardless of their social ranking. Accessibility (visitation) to parks and recreational areas has increased significantly all over the world. This scenario to some extent is the same in Hail city, where the area allocated for parks and open spaces is very small. Parks in Hail are still suffering from many planning and design aspects that discourage people from frequent visitations. This study, therefore, aims to address this phenomenon by examining the area allocated for parks and park attributes. The study’s data are collected from the relevant literature regarding parks and their attributes. An assessment tool is designed and utilized to evaluate parks in Hail. Google maps software was used to measure the areas of neighborhoods and parks in addition to park distribution. This study shows that the areas allocated for parks are far below WHO requirements, and park attributes do not fully meet all visitors’ requirements.